KEPEMIMPINAN KEPALA SEKOLAH DALAM PEMBINAAN PROFESIONAL GURU DI SMK NEGERI TAPANGO SULAWESI BARAT - Muh. Alwy Yusuf; Abdul Saman; Wahira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe and analyze the role of school principal leadership in developing teacher professionalism at SMK Negeri Tapango, West Sulawesi. The research employed a descriptive qualitative method with data collected through in-depth interviews, participatory observation, and documentation. The primary informants included the Principal, Vice Principals, and selected teachers. Data were analyzed through reduction, presentation, and verification using source and method triangulation. The findings reveal that the principal of SMK Negeri Tapango applies a transformational leadership style, combined with a familial and collaborative approach. The principal acts as an inspirator, facilitator, and provides individual support for teachers’ professional growth. Professional development is carried out in a structured and sustainable manner through training, workshops, benchmarking activities, field mentoring, and professional learning communities. These strategies have effectively enhanced the teachers' pedagogical, professional, social, and personal competencies, which in turn have improved their motivation and teaching quality. Supporting factors for successful professional development include government policy support, BOS (School Operational Assistance) funding, strong collegiality among teachers, and the availability of information technology. The main obstacles identified are limited ICT infrastructure, resistance from a minority of teachers to change, and high workloads. The principal addresses these challenges through adaptive approaches, collaborative solutions, and continuous evaluation. This study reinforces the relevance of transformational leadership theory in the context of vocational education and offers a model of best practice for teacher professional development in vocational high schools.